If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1200p + 58 = 500 Reorder the terms: 58 + 1200p = 500 Solving 58 + 1200p = 500 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-58' to each side of the equation. 58 + -58 + 1200p = 500 + -58 Combine like terms: 58 + -58 = 0 0 + 1200p = 500 + -58 1200p = 500 + -58 Combine like terms: 500 + -58 = 442 1200p = 442 Divide each side by '1200'. p = 0.3683333333 Simplifying p = 0.3683333333
| x^2-2ab+2bx^2-a=0 | | 0.3Q^2-4Q-40=0 | | 1x-4yi=4 | | 10-(x+2)=-4 | | 154=256+154 | | 10c-3=37 | | 80=256+80 | | 2x=3+4y | | -5q-4=15 | | 4sin^2*x+1=0 | | 40=256+40 | | Q^2-4Q-40=0 | | 25x^2+20x-21=0 | | 70x-4=0 | | 5x(5x+4)=0 | | 6x^2-12-18x=0 | | 4a-2(3a-5)=3(a-2) | | B/2.4=6 | | Z=ln*(5x^2+4y) | | 10x-6=8+2 | | sen(4x)-sen(2x)=0 | | (x+3)(x-2)=5(x+3) | | 4(x-3)+6(x+10)-15=-22 | | 8-2g+5g+3= | | 4(x-3)+6(x+10)-15=-23 | | 3x(3x^2-10x+3)=0 | | -12h=-60 | | 42=144 | | X+y=4z | | 3x^2+18+24= | | 2a+4=12a+6 | | a*a(a-2b)+3b(a*a-4)= |